2019
DOI: 10.21307/pm-2019.58.2.191
|View full text |Cite
|
Sign up to set email alerts
|

Exopolysaccharide-Producing Lactic Acid Bacteria – Health-Promoting Properties And Application In The Dairy Industry

Abstract: Exopolysaccharides (EPS) are one of the classes of extracellular biopolymers synthesized by bacteria. Some strains of lactic acid bacteria (LAB) used in the dairy industry are able to synthesize EPS (EPS(+) strains). EPS may be secreted by a cell in the form of capsule or slime. Our review describes the factors influencing the activity of EPS production by LAB, the impact of the use of EPS(+) strains on the quality of fermented milk products (yoghurt, cheeses, etc.) and pro-health properties of EPS produced by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 90 publications
(228 reference statements)
0
12
0
1
Order By: Relevance
“…In the case of isolates that showed high or good EPS formation from lactose, they can be used alone or in combination with starter cultures for the production of dairy fermented products, improving rheology and texture, in addition to contributing to their functional properties. A number of studies regarding EPS (+)-producing LAB indicated improvement of aroma, texture, and consistency of cheeses, particularly lowfat cheeses (light), due to retention of water molecules during clot formation, reducing water activity (a w ), and consequently, syneresis (Schmid et al, 2015;Zhang et al, 2015;Ayyash et al, 2018;Wang et al, 2018;Berthold-Pluta et al, 2019). The EPS production by these LAB isolates can also represent an alternative to increase efficiency and yield on cheese production, drawing industries attention to cheaper, more natural, and more sustainable biopolymers, which also have regional characteristics, indicating Serrano (South) and Minas artisanal cheeses from Canastra and Campo das Vertentes microregions (Southeast) as the primary sources of EPS(+)-producing LAB from lactose (Figure 3).…”
Section: Discussionmentioning
confidence: 99%
“…In the case of isolates that showed high or good EPS formation from lactose, they can be used alone or in combination with starter cultures for the production of dairy fermented products, improving rheology and texture, in addition to contributing to their functional properties. A number of studies regarding EPS (+)-producing LAB indicated improvement of aroma, texture, and consistency of cheeses, particularly lowfat cheeses (light), due to retention of water molecules during clot formation, reducing water activity (a w ), and consequently, syneresis (Schmid et al, 2015;Zhang et al, 2015;Ayyash et al, 2018;Wang et al, 2018;Berthold-Pluta et al, 2019). The EPS production by these LAB isolates can also represent an alternative to increase efficiency and yield on cheese production, drawing industries attention to cheaper, more natural, and more sustainable biopolymers, which also have regional characteristics, indicating Serrano (South) and Minas artisanal cheeses from Canastra and Campo das Vertentes microregions (Southeast) as the primary sources of EPS(+)-producing LAB from lactose (Figure 3).…”
Section: Discussionmentioning
confidence: 99%
“…Lowering the pH during the fermentation process of yoghourt can lead to syneresis resulting from destabilisation of casein micelles. In situ production of EPS has been used to overcome this problem, as it leads to better rheological properties than when EPS is added as one of the components [ 92 , 123 ]. The starter cultures used for yoghourt production, Lactobacillus delbruecki subsp.…”
Section: Application Of Eps-producing Lab In Food Productsmentioning
confidence: 99%
“…Exopolysaccharides (EPs) are high-molecular, long-chain linear biopolymers containing side chains of homopolysaccharide or heteropolysaccharide carbohydrate units linked with α-glycosidic and β-glycosidic bonds [98]. The enzymes such as glycosyltransferase and glycoside hydrolase convert the sugar nucleotide precursors into EPs.…”
Section: Exopolysaccharides (Eps)mentioning
confidence: 99%